Concurrent myotomy and tunneling after establishment of a half tunnel instead of myotomy after establishment of a full tunnel: a more efficient method of peroral endoscopic myotomy - George M. Philips; Sunil Dacha; Steve A. Keilin; Field F. Willingham; Qiang Cai (Endoscopy International Open, 2016)
Background and study aims: Peroral endoscopic myotomy (POEM) is a time-consuming and challenging procedure. Traditionally, the myotomy is done after the submucosal tunnel has been completed. Starting the myotomy earlier, after submucosal tunneling is half completed (concurrent myotomy and tunneling), may be more efficient. This study aims to assess if the method of concurrent myotomy and tunneling may decrease the procedural time and be efficacious. Patients and methods: This is a retrospective case series of patients who underwent modified POEM (concurrent myotomy and tunneling) or traditional POEM at a tertiary care medical center. Modified POEM or traditional POEM was performed at the discretion of the endoscopist in patients presenting with achalasia. The total procedural duration, myotomy duration, myotomy length, and time per unit length of myotomy were recorded for both modified and traditional POEM. Results: Modified POEM was performed in 6 patients whose mean age (± standard deviation [SD]) was 58 ± 13.3 years. Of these, 5 patients had type II achalasia and 1 patient had esophageal dysmotility. The mean Eckardt score (± SD) before the procedure was 8.8 ± 1.3. The modified technique was performed in 47 ± 8 minutes, with 6 ± 1 minutes required per centimeter of myotomy and 3 ± 1 minutes required per centimeter of submucosal space. The Eckardt score was 3 ± 1.1 at 1 month and 3 ± 2.5 at 3 months. The procedure time for modified POEM was significantly shorter than that for traditional POEM. Conclusions: Modified POEM with short submucosal tunneling may be more efficient than traditional POEM with long submucosal tunneling, and outcomes may be equivalent over short-term follow-up. Long-term data and randomized controlled studies are needed to compare the clinical efficacy of modified POEM with that of the traditional method.